Design a radio receiver for solar activity observation in VLF band - Al Banna, Ahmed (Al-Khwarizmi Engineering Journal, 2023)
Solar activity monitoring is important in our life because of its direct or indirect influence on our life, not only on ionospheric communications. To study solar activity, researchers need measuring and monitoring instruments, these instruments are mostly expensive and are not available in all universities. In this paper, a very low frequency radio receiver had been designed and implemented with components available in most markets to support the researchers, college students, and radio astronomy amateurs with a minimum input voltage less than 100µV, an output voltage less than 135 m V with no distortion and an overall gain of 34dB. A comparison had been done between two circuit structures using a workbench software program and experimentally done in the lab. Two antennas were experimentally tested and a loop antenna was chosen. The whole system was connected and tested to receive signals in the Lab and monitored on computer using HDSDR software program. Another experiment done outside the lab (at home), and the result was not good because of many high level interference noises.